Fidelity of replication of phage phi X174 DNA by DNA polymerase III holoenzyme: spontaneous mutation by misincorporation. - Fersht, A R (1979)
DNA from phi X174 is replicated in vitro with a fidelity similar to that found genetically. A mutation of TAG leads to TGG may be induced, however, by varying the concentrations of deoxynucleoside triphosphates, with a frequency proportional to [dGTP]2/[dATP]. This complex concentration dependence is consistent with the active participation of a proofreading mechanism that hydrolytically excises mismatched base pairs as they are formed. A simple kinetic analysis predicts that the frequency of misincorporation depends on the ratio of incorrect to correct deoxynucleoside triphosphates times the concentration of the next triphosphate in the sequence to be added. This suggests that spontaneous mutation by misincorporation depends crucially on the composition of the deoxynucleoside triphosphate pool.